Necessity of Accreditation Standards for Quality Assurance of Medical Basic Sciences - J Jahroomi Shirazi; N Nakhaee; Z Jalili; M Rezaeian; AR Jafari (Tehran University of Medical Sciences, 2013)
Background: The present article reviews the significance of accreditation standards while emphasizing the necessity of implementation of such standards by basic medical science council, with an eye on such international standards as those published by WFME. This review article had to decide on the key words and expressions, data bases, to review relevant literature, review higher and medical education journals at GOOGLE, ELSEVIER, PUBMED, and such web sites as those of WFME and WMA's. Accreditation is a powerful leverage for institutional change and improvement and must be actively supported by academic and national health authorities worldwide. Considering the mission of the Basic Medical Science, Health and Post grad. Education, Ministry of Health and Medical Education, Tehran, Iran as accountable medical education, all specialists of the spectrum of disciplines agreed on the necessity of formulating the medical education standards for all disciplines of their interest. It is important that all efforts be joined in the endeavor to create effective and reliable instruments for quality assurance of Basic Medical Sciences Education.